(untitled) (Journal of NELTA, 2011)
In this article I begin by exploring ideas of sustainability and the emergence and prevalence of this term into international discourse. I then outline the connection between learning and sustainability and the emerging field of Education for Sustainability (EfS). I go on to draw parallels between EfS and English Language Teaching (ELT) suggesting that what, how, who and where we teach, gives us an exciting role to play in this emerging paradigm of education and wider societal changes- why we teach. I finish by making suggestions for strengthening this connection. Key words: Sustainability; English for sustainability; Teaching English Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 16-21 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4605